CHALLENGES OF PONDOK EDUCATIONAL INSTITUTION AND IT’S IMPACT ON STUDENTS DEVELOPMENT - Ramiaida Darmi; Mohd Muzhafar Idrus; Hazlina Abdullah; Maziahtusima Ishak; Adibah Sulaiman; Hayati Ismail; Zulkiple Abd Ghani; Noornajihan Jaafar; Siti Rugayah Hj Tibek; Amir Husin Mohd Nor; et al. (Journal of Islamic, Social, Economics and Development, 2017)
: The pondok educational system is an institution of Islamic religion that exists and is recognized by the community. It plays a role in spreading religious knowledge and forming a perfect Muslim personality. The Islamic education applied in the study is one of the most important channels to shape character and thinking in parallel with Islamic values. Lack of understanding of Islamic teaching will lead a person to behavior that is contrary to Islam. Hence, the purpose of this study is to identify the challenges faced by the pondok education institution as well as to study the impact of students following the curriculum system to themselves. This study uses qualitative and quantitative methods through document analysis and interviews via round table discussions with the authority individuals and distribution of questionnaire. A total of 233 respondents were selected from several pondok in Peninsular Malaysia. The findings show that there are three main factors that challenge the development of the present cottage curriculum, management and the recognition of cottage studies. The findings also found that students acknowledged that this education system had a positive impact on themselves (mean 4.59). They also acknowledged that this education system benefited their families and their environment. In conclusion, pondok education system seeks to create better student orientation and produce quality students.